„Wyrastają w dyskomforcie” – o wystawach sztuki współczesnej w ramach cyklu „Cloakroom” w krakowskiej Cricotece ………. 301 (Sceny kultury: Teksty ofiarowane prof. Krzysztofowi Pleśniarowiczowi, 2026)
“GROWING UP IN DISCOMFORT”: ON CONTEMPORARY ART EXHIBITIONS IN THE “CLOAKROOM” SERIES AT CRICOTEKA IN KRAKOWThis article examines the origins, development, and significance of the alternative exhibition program “Cloakroom,” held from 2021 to 2024 at Cricoteka in Krakow on the initiative of curator Kamil Kuitkowski. Housed in the building’s former cloakroom and deliberately operating within a space of “the lowest-ranking reality,” this series creates a non-hierarchical platform for presenting contemporary art, particularly that of the younger generation of artists. Subsequent editions of “Cloakroom” demonstrate how, in dialogue with Tadeusz Kantor’s legacy – particularly his reflections on memory, trauma, transience, and the human condition – new forms of expression emerge that address themes of war, violence, childhood, phantasmality, and institutional crises. The article reconstructs the circumstances of the project’s creation, situates it within the context of changes in the artistic field in Krakow, and analyzes the three subsequent editions of the series. It also highlights the role of “Cloakroom” as an experimental space that, by situating itself on the margins of official narratives, becomes a place of creative risk, discomfort, and resistance to established expectations regarding a monographic institution. This program demonstrates that Cricoteka is not merely a place of remembrance for Kantor, but a living institution open to contemporary artistic practices that are critical of tradition while simultaneously emerging from it.